Leadership Coaching as Design Conversation - Sherryl Stalinski (International Journal of Evidence Based Coaching and Mentoring, 2004)
This paper seeks to bridge and integrate the disciplined and rigorous practice of Design Conversation with the professional practice of coaching within the organisational setting. Argument is made that coaching is uniquely positioned to serve as a tool and process for facilitating genuine and effective dialogue at the organisational level. It explores current literature, understanding and issues in the areas of organisational learning, systems research, dialogue practice in organisations, and coaching as a professional practice. In conclusion, the article suggests that a design conversation of vested stakeholders is needed to further explore and synthesize the integration of dialogue, conversation, and leadership coaching.